PERAN FORUM PEMBAURAN KEBANGSAAN BADAN KESATUAN BANGSA DAN POLITIK KABUPATEN SINTANG - Syamsudin, Martinus (Universitas Kapuas Sintang, 2024)
The study in this study is the Role of the National Integration Forum of the National Unity and Politics Agency of Sintang Regency. and therefore the objectives to be achieved in this study are to find out, describe and analyze. With this research method using Descriptive research. The subjects in namely the Head of the Agency, the National Unity Development Section, the Chairperson of the FPK and FPK Members, with the research techniques used in data collection are observation, interviews and documentation studies with data analysis using qualitative descriptive analysis methods. The results of this study indicate that (1). The role of the FPK has carried out its role in supporting existing policies and trying to comply with all applicable provisions regarding the implementation of programs in the field of Ideology and National Insight Development. (2). FPK development is running well but after the Covid-19 pandemic there is a budget problem in implementing the national insight program because the budget for implementing the national insight program is diverted to handling Covid-19 so that several programs have not run optimally. The suggestions submitted by the Research are (1). The role of FPK which has carried out its role in supporting existing policies and has attempted to comply with all applicable provisions regarding the implementation of programs in the field of Ideology and National Insight Development so that it continues to be improved. (2). FPK development which has been running well but has not yet run optimally so that it can be improved and continue to improve the work program.